2020
DOI: 10.1103/physrevlett.124.047203
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Domains without Domain Walls: A Unique Effect of He+ Ion Bombardment in Ferrimagnetic Tb/Co Films

Abstract: We show that it is possible to engineer magnetic multi-domain configurations without domain walls in a prototypical rare earth/transition metal ferrimagnet using keV He + ion bombardment. We additionally shown that these patterns display a particularly stable magnetic configuration due to a deep minimum in the free energy of the system which is caused by flux closure and the corresponding reduction of the magnetostatic part of the total free energy. This is possible because light-ion bombardment differently af… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…These compensation points lead to useful phenomena, such as fast domain wall motion [32,33], thermally induced switching [34,35], vanishing skyrmion Hall angles [36], and self-focusing skyrmion racetracks [37], while efficient spin-orbit torque switching around compensation has been observed in studies of RE:TM alloys with bulk perpendicular anisotropy (PMA) [38][39][40][41][42], the onset of which may be controlled by the RE content [43]. Recently, it has also been shown that domain walls and compensation temperatures can be altered with ion bombardment [44].…”
mentioning
confidence: 99%
“…These compensation points lead to useful phenomena, such as fast domain wall motion [32,33], thermally induced switching [34,35], vanishing skyrmion Hall angles [36], and self-focusing skyrmion racetracks [37], while efficient spin-orbit torque switching around compensation has been observed in studies of RE:TM alloys with bulk perpendicular anisotropy (PMA) [38][39][40][41][42], the onset of which may be controlled by the RE content [43]. Recently, it has also been shown that domain walls and compensation temperatures can be altered with ion bombardment [44].…”
mentioning
confidence: 99%
“…For tailoring magnetic patterns in magnetic thin film systems three classes of methods are currently known: (1) thermal patterning 9 by a tip of a scanning force microscope, (2) laser patterning [10][11][12] , and (3) patterning by light keV-ions 13,14 . In the present work we will focus on consequences of recent results, where it has been found that domains without domain walls (DWs) can be created in Tb/Co ultra-thin layer systems by bombardment with keV-He + -ions 15 . In the present context, by domains in ferrimagnetic films we understand regions with distinct effective magnetization orientation and by DW we denote the transition region between two such domains with a continuously rotating magnetization of both subsystems [15][16][17] .…”
mentioning
confidence: 99%
“…In the present work we will focus on consequences of recent results, where it has been found that domains without domain walls (DWs) can be created in Tb/Co ultra-thin layer systems by bombardment with keV-He + -ions 15 . In the present context, by domains in ferrimagnetic films we understand regions with distinct effective magnetization orientation and by DW we denote the transition region between two such domains with a continuously rotating magnetization of both subsystems [15][16][17] . With these definitions in mind, it is possible to conceive magnetic configurations realizable in ferrimagnetic heterostructures with regions of different subsystem domination.…”
mentioning
confidence: 99%
See 2 more Smart Citations